2019
DOI: 10.1177/1043454219835451
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Promote Oral Medication Adherence in the Pediatric Chronic Illness Population: A Systematic Review From the Children’s Oncology Group

Abstract: Children and adolescents diagnosed with cancer often require treatment that includes oral medications. These oral medications frequently include both antineoplastic agents essential to cancer treatment and associated supportive care medications. Oral chemotherapy and supportive care regimens are often administered by the child or parent at varied dosing schedules, often for prolonged periods of time (Landier, 2011b). Thus, medication management is an important topic to be addressed with newly diagnosed patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Physician reviewers (Table 3) selected improved communication as a strategy that could have prevented all of errors in this study; specifically, between caregivers and the health system to avoid home administration errors or among members of the health system (e.g., pharmacy, clinician) to prevent prescribing or dispensing errors. Interventions, such as apps or paper materials, are clearly needed to support communication between caregivers at home 2,36 …”
Section: Discussionmentioning
confidence: 99%
“…Physician reviewers (Table 3) selected improved communication as a strategy that could have prevented all of errors in this study; specifically, between caregivers and the health system to avoid home administration errors or among members of the health system (e.g., pharmacy, clinician) to prevent prescribing or dispensing errors. Interventions, such as apps or paper materials, are clearly needed to support communication between caregivers at home 2,36 …”
Section: Discussionmentioning
confidence: 99%
“…Forgetfulness and a lack of social support could affect compliance to oral medication in chronically ill pediatric patients. [ 62 ] One possible future application of our method in pediatric patients could be in sickle cell disease (SCD), where many European countries, the U.S.A. and Canada implemented newborn SCD screening programs. [ 63 , 64 ] Our method would not only allow to non‐invasively monitor iron dosage and chelation therapy (Figure S9F , Supporting Information), but could also increase therapy adherence through gamification [ 65 , 66 ] (Figure S9G , Supporting Information) and fewer invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
“… Ruddy et al (2009) and Stinson et al (2012) argue that discussing the importance of adherence has also been found to be beneficial, as it may spur those with poor adherence to improve and may encourage those with good adherence to continue. Along with this, they stated that TYAs must be educated in their treatment regimes, to fully understand what they are taking and why ( Coyne et al, 2019 ; Ruddy et al, 2009 ; Stinson et al, 2012 ). The National Service Framework for Children ( Department of Health, 2004 ) advocates this shared decision-making between parents or carers, children or young people, and professionals.…”
Section: Discussionmentioning
confidence: 99%
“…The active inclusion of the TYAs in this dialogue regarding treatment helps set an atmosphere of compliance. It can improve the professional–patient relationship from compliance (doctor's recommendations) through to adherence (sticking to the plan) to concordance (harmonizing) ( Coyne et al, 2019 ; Horne et al, 2005 ; Windebank & Spinetta, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation